Bildad’s Contribution to the Debate—A New Interpretation of Job 8:17–19 - Pinker, Aron (Vetus Testamentum, 2016)
This paper claims that in unit 8:16-19 Bildad attempts to answer the fundamental question: If Job and his children were “wild plants in the garden,” why weren’t they taken care of by society’s normal restraining arms, and there was need for heavenly intervention, which acts without explanation? The answer given focuses on the environmental support enjoyed by the wicked, their resilience, and their capability to revivify. Only God is capable to completely eradicate the wicked. This appears to be Bildad’s original contribution to the debate.